Aktualisasi Nilai Berkebhinekaan Global pada Perilaku Siswa Kelas IV di SD Negeri 34 Parit Madura (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the actualization of the value of global diversity in the behavior of grade IV students at SD Negeri 34 Parit Madura. The research method used is a calytic method with a descriptive approach. The data collection technique in this study uses observation and documentation techniques. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of this study show that grade IV students of SD Negeri 34 Parit Madura show positive results in various aspects of diversity attitudes. The attitude of knowing and appreciating other cultures obtained an average of 80%, indicating that most students are able to appreciate and accept cultural, religious, and ethnic diversity. Intercultural communication skills are also excellent with an average of 88%, reflecting students' skills in interacting effectively with various cultural backgrounds. Openness and tolerance reached an average of 79%, indicating students' readiness to learn from different perspectives and adjust to a multicultural environment. Finally, attitudes of reflection and responsibility towards diversity experiences reached an average of 87%, indicating students' understanding of human rights and rejection of discrimination. Overall, students showed a strong and positive attitude in applying the value of diversity